A Study on Trust in Media and its Relationship with Interest and Exposure of Advertising - Leung, Chi Hong; Chan, Winslet Ting Yan (Asian Journal of Empirical Research, 2019)
Consumers receive numerous advertising messages from both online and offline media. Online media are becoming popular because they are convenient and easy to access although users may not trust them as much as the offline media. A total of 109 respondents participated in a survey on their interest and trust in various online and offline media. There are diverse attitudes to different online media. Facebook (as an example of social media) and official webpages (as examples of owned media) are the most interesting and trusted online media while blogs (as examples of informal diary style textual posts) and eBay (as an example of e-commerce platform) are the least interesting and trusted online media. In addition, trust and interest in media are found to be moderately correlated. Thus, consumers feel interested in advertising on trusted media. Besides, the result of the perceived truthiness test with 92 subjects reveals that repeated exposure to product information cannot increase the degree of trust in advertising messages. To choose a suitable medium for advertising is more important than increasing the frequency of advertising.